The Perspectives and Practices on Sustainable Development of SIDS - Goede, Dr. Miguel (IJRDO - Journal of Social Science and Humanities Research, 2016)
Purpose – The purpose of this article is to describe how Caribbean Small Island Developing States (SIDS) implemented the Millennium Development Goals (MDG), the lessons learned during implementation, and to be applied when implementing the Sustainable Development Goals (SDG). Methodology/Approach – For this study, a literature review was conducted and interviews were held with key figures. The draft version was send to key persons for feedback in all thestudied SIDS, and other researchers in the field of SIDS. Findings – In general the Caribbean SIDS have not dealt well with the MDG. The MDG were inadequately institutionalized, and the statistical data to monitor the progress was insufficient. It does not look like they are applying lessons learned to the SDG process in asystematic way. Originality/value of paper – The paper contributes to the analysis of policy implementation in Caribbean SIDS. It presents lessons learned that might make the implementation of SDG more successful.